The Impact of War on The Cryptocurrency Economy from a Management Perspective - Suryari Purnama; Bayu Laksma Pradana; Gautam Khanna; Suhandi Suhandi; Agung Rizky; Ihsan Nuril Hikam; Muhammad Farhan Kamil (International Institute for Advanced Science & Technology (IIAST), 2024)
Armed conflicts and wars are increasingly shaping the global economic landscape, impacting both traditional markets and the burgeoning cryptocurrency economy. Cryptocurrencies, underpinned by blockchain technology, hold revolutionary potential for transactions, investments, and trading. However, their decentralized and global nature leaves them vulnerable to external shifts, particularly geopolitical events like war. This research explores the influence of war on cryptocurrency from a management perspective, analyzing how conflict impacts regulation, investment patterns, and technology adoption within the cryptocurrency ecosystem. By employing a literature based approach, this study aims to elucidate how global political and security shifts affect the cryptocurrency market. The findings indicate high reliability in the observed variables Investor, Crypto Market, and War with Cronbach alpha values ranging from 0.832 to 0.878, and rhoA values between 0.860 and 0.881. Additionally, composite reliability scores are robust, ranging from 0.860 to 0.882, demonstrating strong measurement reliability. The Average Variance Extracted (AVE) values, between 0.603 and 0.673, confirm that these measurement variables significantly explain the variance of the latent constructs. These results underscore the efficacy of the developed model in analyzing the interplay between war and cryptocurrency markets, contributing valuable insights into the sector resilience and adaptability amid geopolitical conflicts.